Adsorção de nitrato em rejeito de caulim organofuncionalizado com uréia - TAVARES, Laís Conceição (Universidade Federal do Pará, 2019)
Kaolin waste, generated in abundance by companies from Pará state, has caused to the environmental problems. In order to give input on the reuse of this waste was evaluated retention of nitrate ions on kaolin waste natural and modified with urea and studied the equilibrium of adsorption processes at solid-solution interfaces. The materials were characterized by X-ray diffraction and X-ray fluorescence (XRF and XRD, respectiely), IR spectroscopy (FTIR spectrum), scanning electron microscopy and estimated data of surface charge. Adsorption experiments of nitrate ions in the waste natural kaolin (CRJN) and modified with urea (CRJU) were performed without pH adjustment. H + concentrations were measured by direct potentiometry before and after the process of adsorption and equilibrium concentrations of nitrate were measured by ion chromatography. The results indicated: high purity kaolin waste; formation of kaolinite-urea complex confirmed by XRD reflection at 2  8,28o e d = 1.068 nm and the FTIR spectrum with the appearance of a broad band of low intensity, containing two discrete shoulder around 3500-3380 cm-1, corresponding to asymmetric and symmetric vibrations of the group-NH2 of urea-kaolinite, superimposed to the vibration of water. surface charges data, suggesting that the materials have a higher capacity to adsorb cations than anions, but depending on the concentration of H + and OH- on adsorbent, the hydroxyl surface can be protonated yielding positive charges that are reflected in the adsorption of anions, obtaining significant adsorbed nitrate, both in CRJN as CRJU (0,27-0,73 and from 0,18-0,70 3.5 mg g-1, respectively), the separation coefficient (RL) of from 0,28 to 0,828 change in free energy ΔG ° = -2,094 to + 0,445 kJ mol-1 for CRJN and ΔG° = -1,036 to + 1,32 kJ mol-1 for CRJN molecule. The data from RL indicated that the adsorption processes are less favorable in most points of the adsorption processes and based on the results of the free energy change (ΔG º) was showed low spontaneity to no spontaneity and adsorption processes are physical.